PID Control for a Pneumatic Servo System - Tran, Xuan Bo (Old Journal, 2019)
This paper examines the position control ability of a pneumatic cylinder in pneumatic servo system using PID control method. A pneumatic servo system including a pneumatic cylinder and 02 proportional flow control valves is firstly proposed. The system is then modeled by dynamic equations with consideration of the valve characteristics and of friction in the pneumatic cylinder. Proportional-Integral-Derivative controller (PID) is applied to control the cylinder position. Effects of the external load and the source pressure to the control ability of the PID controller are considered. Simulation and experimental results show that the PID controller gives good control performances under different operating conditions of the external load and the air source pressure.